Interaction between HIV protease inhibitors (PIs) and hepatic transporters in sandwich cultured human hepatocytes: implication for PI‐based DDIs. (4th March 2013) - Liu, Li; Unadkat, Jashvant D.
ABSTRACT Although HIV protease inhibitors (PIs) produce profound metabolic interactions through inactivation/inhibition of CYP3A enzymes, their role as victims of transporter‐based drug–drug interactions (DDIs) is less well understood. Therefore, this study investigated if the PIs, nelfinavir (NFV), ritonavir (RTV), lopinavir (LPV) or amprenavir (APV) were transported into sandwich‐cultured human hepatocytes (SCHH), and whether OATPs contributed to this transport. The findings showed that, except for 3H‐APV, no significant decrease in the total hepatocyte accumulation of the 3H‐PIs was detected in the presence of the corresponding unlabeled PI, indicating that the uptake of the other PIs was not mediated. Further, hepatocyte biliary efflux studies using 3H‐APV and unlabeled APV confirmed this decrease to be due to inhibition of sinusoidal influx transporter(s) and not the canalicular efflux transporters. Moreover, this sinusoidal transport of APV was not OATP‐mediated. The results indicate that the hepatic uptake of NFV, RTV or LPV was primarily mediated by passive diffusion. The hepatic uptake of APV was mediated by an unidentified sinusoidal transporter(s). Therefore, NFV, RTV or LPV will not be victims of DDIs involving inhibition of hepatic influx transporters; however, the disposition of APV may be affected if its sinusoidal transport is inhibited. Copyright © 2013 John Wiley & Sons, Ltd.